Manajemen Presensi Berbasis NFC (Near Field Communication) di GMIM Imanuel Bahu - Diamanis, Axellindo; Rindengan, Yaulie D.Y.; Manembu, Pinrolinvic D.K. (Jurnal Teknik Informatika, 2022)
Digital based attendance system in today's modern era there are various kinds of technology used. NFC (Near Field Communication) is one of the newest technologies utilizing radio waves. Near Field Communication (NFC) technology until now is growing, it has made it possible to transfer data wirelessly with electronic-based cards or NFC tags. To maximize the NFC-Based Presence in GMIM Imanuel Bahu a Card Reader Device and also a website-based application are required to manage the data. The system aims to make it easier for the congregation to enter the church by not manually filling in the data and to make it easier for admins or church employees to manage the attendance of the congregation in detail.